Asian perspectives and evidence on health promotion and education - Muto, Takashi; Nakahara, Toshitaka 1949-.; Nam, Eun Woo.; SpringerLink (Online service).; Asia-Pacific Conference on Health Promotion and Education Chiba, Japan) 2009 (Tokyo New York Springer, 2011)
Globalization and information technology have caused many health problems: mental health issues like depression, and lifestyle-related disease like diabetes and obesity. To cope with these health issues, health promotion and education are desperately needed. Convincing policy decision makers to invest in health promotion and education programs, it is needed to show its effectiveness. Health promotion and education professionals are expected to construct evidence of health promotion and education. Most of such evidence has been produced in the US and European countries. Because socio-economic conditions differ between the Asia and Western countries, we cannot depend on such evidence to implement adequate health promotion and education in our region. We must produce and accumulate our own evidence based on Asian perspectives.
Japan's current health issues and health promotion in the community setting: focus on public health nurses' activities -- Outcomes of lifestyle improvement programs in the last ten years in Asia -- Health promoting schools in Taiwan: present status and future perspectives -- Workplace health promotion in Korea -- Characteristics of workplace health promotion in Japan -- Tokyo gas health promotion program -- Evidence of physical activity for disease control and health promotion -- Using computer-tailored technology to promote physical activity and healthy eating: a review of the literature and Asian-Pacific evidence -- Dietary lifestyle interventions of energy restriction for weight control and salt reduction for prevention of hypertensive risk in Asian adults -- Building capacity in smoking cessation counseling among health care professionals in China -- Issues of Korean alcohol policy perspectives -- Current status and prevention of obesity -- Waist-to-height ratio is the best anthropometric index for screening the risk of obesity-related disorders -- Health promotion and education based on the features of cardiovascular disease in Asia -- Prevention and psychological intervention in depression and stress-related conditions -- Principles and activities of oral health promotion in Asian countries -- New development in education to prevent sexual transmitted infections, especially HIV/AIDS: actual practice of sexuality health education by means of peer counseling approach -- School-based safety promotion in Japan -- "Safe community" in Asia: safety promotion based on injury prevention.
"This is a collection of papers written by eminent participants at the First Asia-Pacific Conference on Health Promotion and Education ... held in July 2009 in Chiba, Japan."--Preface, p. v.
Electronic reproduction.
Keywords: Health education -- Asia -- Congresses; Health promotion -- Asia -- Congresses; Health education -- Law and legislation -- Asia -- Congresses; Health promotion -- Asia -- Congresses; Health education -- Asia -- Congresses; Congresses; Electronic books